Numerical simulation of impact response for pantograph slide plate - Caizhi Yang; Peihuo Peng; Like Pan; Liming Chen; Fan He (Scientific Reports)
Abstract As a key component, the performance of pantograph slide plate is directly related to the normal operation of train and the stability of power supply. The pantograph slide plate is exposed to the complex environment and thus it would face mechanical impacts. In this paper, two types of slide plate models (wide and narrow) are constructed to explore the mechanical behavior of pantograph slide plate under impact using the finite element method. The results show that the slide plates rapidly deform at the beginning of the impact, and then the stress variation speed gradually slows down and tends towards a stable and low amplitude of self vibration. Under strong impact, the vibration frequency and amplitude of the slide plate significantly increase. The stress level of wide slide plate is lower than that of narrow slide plate. Narrow slide plate exhibits higher sensitivity and instability. This indicates that when the train is running at a high speed, factors such as track irregularities and airflow disturbances have a more significant impact on the narrow slide plate. This work provides valuable references for subsequent optimization design.